GAMBARAN KEJADIAN SUB INVOLUSI UTERI PADA IBU NIFAS DI POLINDES BUGIH II WILAYAH KERJA PUSKESMAS KOWEL - Mardiana Mardiana; Emi Yunita (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2021)
The postpartum period is the period that begins after the placenta comes out and ends when the uterine organs return to their original state (before pregnancy). One of the complications that can occur during the puerperium is uterine subinvolution, where the uterus fails to follow the normal pattern of involution as it should. So that the process of uterine shrinkage is hampered. Based on data obtained at Polindes BugihII in 2014 out of 10 postpartum mothers at 2-6 weeks, 7 (70%) postpartum mothers had uterine subinvolution and 3 (30%) did not. The purpose of this study was to describe the incidence of uterine subinvolution in postpartum mothers at Polindes Bugih II. This research design is descriptive. The total population in this study were 30 postpartum mothers, while the sampling used probability sampling with saturated sampling technique. The variable in this study was the incidence of uterine subinvolution in postpartum mothers. The research instrument used the MCH handbook, then analyzed using univariate analysis. The results of the study were almost entirely (76.67%) mothers did not experience uterine subinvolution, namely as many as 23 people. The solution that can be done to overcome this incident is to encourage the mother to move and breastfeed her baby as often as possible, because this will affect the hypothalamus and cause contractions. So that from these contractions will result in uterine involution and expenditure of Lochea running normally. It is also recommended for multiparous mothers to participate in family planning programs.